2022
DOI: 10.1097/hpc.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Angiographic and Clinical Outcomes After Primary Percutaneous Coronary Intervention for ST-elevation Myocardial Infarction Between Patients With and Without Concomitant COVID-19 Infection

Abstract: Objective: COVID-19 infection can involve the cardiovascular system and worsen the prognosis of the patients. This study aimed to investigate the adverse effects of COVID-19 on angiographic and clinical outcomes of primary percutaneous coronary intervention (PCI) in patients with acute ST-elevation MI and compare results with those patients without COVID-19 disease. Methods: The study was a retrospective observational cohort, in which patients presented with ST-elevation MI from February 2020 to April 2021, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Title and abstract screening of 1075 records based upon our inclusion and exclusion criteria resulted in 92 full texts for further screening. We included 4 papers together with another 2 papers from manual search, in addition to another 5 papers from the search update 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening of 1075 records based upon our inclusion and exclusion criteria resulted in 92 full texts for further screening. We included 4 papers together with another 2 papers from manual search, in addition to another 5 papers from the search update 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 4 According to an angiographic study, patients with COVID-19 infection had worse thrombolysis in myocardial infarction flow grade at baseline and after PCI. 10 As shown in Figure 5 , case 3 had multiple microthrombi in intramyocardial microvessels, which is likely one of the main causes of elevated cardiac troponin in the setting of COVID-19 infection and portends a poor prognosis. Furthermore, as shown in Figure 5E , microthrombi IHC in case 3 showed that they were strongly positive for CD61, fibrin II, D-dimer, and C5b-9.…”
Section: Discussionmentioning
confidence: 96%
“…Due to the high risk of staff contamination, TEE should be avoided as much as possible and be limited to occasions when there are crucially suspicious findings or when it might change the treatment approach. 22 The decline in hospitalization length has been a worldwide issue since the start of the pandemic, 14 , 16 , 17 , 23 representing physicians’ and patients’ inclination toward an early discharge, as well as hospitals’ endeavors to ensure bed availability.…”
Section: Discussionmentioning
confidence: 99%